Sitophilus granarius responses to blends of five groups of cereal kernels and one group of plant volatiles. (May 2015) - Piesik, Dariusz; Wenda-Piesik, Anna
Abstract: In this paper we report the behavioral responses of granary weevil to 6 blends of cereal volatiles. Four doses (1 ng min −1, 10 ng min −1, 100 ng min −1, and 1000 ng min −1 in 50 μl of hexane applied on filter paper) were tested. A Y-tube experiment revealed that females and males of Sitophilus granaries were attracted to the blend 1, 4, and 5 at concentrations of 10 and 100 ng min −1, 10 ng min −1, 1 and 10 ng min −1, respectively. Moreover, females and males of granary weevil were not attracted to any concentration of blend 2 and 3. Yet, the weevil females and males were repelled by the highest concentrations (100 and 1000 ng min −1 ) for all tested blends, except of blend 1, where concentration 100 ng min −1 was an attractant for both sexes. Moreover, females and males were repelled by three tested concentrations of blend 6 (10, 100 and 1000 ng min −1 ). Highlights: Sitophilus granarius display innate behaviors in response to blends of VOC. Blends of VOC are of importance for the positive or negative reaction of insects. Blends are attractants at low and repellents at high concentrations. VOC even not typical for cereal kernels can work as repellents for insects.